Юридичний зміст і структура права апеляційного оскарження рішення - Теремецький, В. І.; Teremetskyi, V. I. (Право і безпека. - 2014. - № 4 (55). - С. 219-224, 2014)
Розглянуто теоретичні засади реалізації права апеляційного оскарження рішення у цивільному судочинстві України. Охарактеризовано структуру права апеляційного оскарження та визначено етапи його реалізації. Проаналізовано право апеляційного оскарження судового рішення у вузькому та широкому значенні. Сформульовано визначення поняття «право апеляційного оскарження рішення в цивільному судочинстві».

Theoretical principles of the right on judgment’s appeal in civil proceedings of Ukraine are studied. It is found out that the right on appeal under the Civil and Procedural Code of Ukraine is not limited either by the number of persons or the cost of the claim or the character of an appeal or obtaining the permission of a court (judge). It is emphasized that there are such judiciary principles in the domestic civil proceedings as equal access to justice and freedom of court judgments’ appeal. The structure of the subjective right on judgment’s appeal is characterized. It includes the following powers: submission of appeal to the court, additions and amendments thereto, the requirement concerning receiving an appeal by the court of the first instance and court of appeal filed by the person or his/her representative, appeal’s court hearings and adoption of a certain judgment by a court of appeal according the filed appeal. The objective of the article is to reveal the legal content of the right on judgment’s appeal in civil proceeding of Ukraine, in particular, to formulate the mentioned right’s definition, to clarify the stages of its realization and to determine its structure. The methodological basis of the thesis is a set of general, special and law methods of scientific cognition. The conceptual apparatus is deepened with the help of logical and semantic method and the method of ascent from the abstract to the concrete. Comparative and legal method allowed us to study the features of the limits in realizing the right of judgment’s appeal according the number of persons, character and price of an appeal within the procedural legislation of foreign countries. The right on judgment’s appeal in the narrow and broad sense is analyzed. The definition of the concept «the right on judgment’s appeal in civil proceedings» is formulated.

Рассмотрены теоретические основы реализации права апелляционного обжалования решения в гражданском судопроизводстве Украины. Охарактеризована структура права апелляционного обжалования и определены этапы его реализации. Проанализировано право апелляционного обжалования судебного решения в узком и широком смысле. Сформулировано определение понятия «право апелляционного обжалования решения в гражданском судопроизводстве».
Legal content and structure of the right on judgment’s appeal
Юридическое содержание и структура права апелляционного обжалования решения
Keywords: право апеляційного оскарження; апеляційне провадження; апеляційна скарга; гарантія; цивільне судочинство; right to appeal; appellant legal procedure; appeal; guarantee; civil justice; право апелляционного обжалования; апелляционное производство; апелляционная жалоба; гарантия; гражданское судопроизводство